Eutectic hydrated salt composite phase change material for enhancing thermal safety of batteries - Guo, Zikai; Zhou, Zixiong; Li, Xinxi; Yin, Likun; zhang, Shuangyi; Yang, Wensheng; Wu, Yuhang; Wu, Di; Li, Canbing (Applied thermal engineering, 2025)
•Hydrated salt composite phase change material (HSCPCM) for battery pack has proposed.•Binary eutectic HSCPCM can mitigate the supercooling for battery thermal safety.•The latent heat loss of HSCPCM is reduced by adding superabsorbent polymer.•The cycling stability of HSCPCM is enhanced via synergistic encapsulation.•Battery module with HSCPCM can balance temperature and suppresses thermal runaway. Lithium-ion batteries (LIBs) face serious safety threats owing to their susceptibility to thermal runaway (TR), particularly under extreme operating conditions, which compromise the reliability of electric vehicles and energy storage systems. Herein, an innovative inorganic hydrated salt composite phase change material (HSCPCM) has proposed for the thermal management of battery modules, aiming to improve the safety of LIBs under both normal operating conditions and TR scenarios. The developed binary eutectic system (DPES2), composed of disodium hydrogen phosphate dodecahydrate and sodium thiosulfate pentahydrate, substantially reduces supercooling. Additionally, the incorporation of polyacrylic acid sodium, expanded graphite, and superabsorbent polymer addresses phase separation, leakage, and cycling stability issues. Experimental results demonstrate that the optimized DPES2 demonstrates excellent thermal management and effectively suppresses TR for battery module, reducing the risk of fires and explosions at high temperatures. Therefore, this research suggests that the inorganic synergistic strategy can achieve dual-level thermal regulation by integrating latent heat storage with thermochemical heat storage to ensure long-term cycling stability. These findings suggest that the HSCPCM offers a practical solution for enhancing the safety and reliability of power batteries and energy storage systems.